دراسة التحكم بمصادر التلوث النقطية واللا نقطية في بحيرة سد الثورة باستخدام برنامج الـ GIS - سلمان, هناء; إسماعيل, خزامى (Latakia University Journal -Engineering Sciences Series, 2017)
لوحظ مؤخراً تدهور جودة مياه بحيرة سد الثورة بسبب زيادة تراكيز المغذيات التي تصل إليها من مصادر نقطية وأخرى غير نقطية. استخدمت نظم المعلومات الجغرافية GIS على نطاق واسع في العقود الأخيرة في عمليات تقييم جودة المياه بالاعتماد على موديلات تعمل ضمن بيئة الـGIS منها الـ (Best Assessment Science Integrating Point and Nonpoint sources) BASIN الذي استخدم في هذا البحث وتم تقدير حمولات التلوث باستخدام أحد نماذج الـ BASIN وهو نموذج الـPload ( (Pollution load.تم تطبيق النموذج باستخدام صورة فضائية لمنطقة الدراسة و نموذج ارتفاعي رقمي DEM30 (Digital Elevation Model) و خريطة استخدامات الأراضي بالإضافة إلى قيم معاملات التصريف وحساب حمولات التلوث السنوية الكلية ضمن الحوض الساكب. تبين أن المساحة الأكبر من الحوض الساكب مزروعة زيتون وحمضيات بنسبة 31%، وأن الأراضي الصخرية المزروعة بالمحاصيل هي المساهم الأكبر في حمولة الفوسفور بنسبة 30%, أما بالنسبة لحمولة النتروجين تعتبر الأراضي المزروعة زيتون وحمضيات هي المساهم الأكبر بنسبة 33%، معدل حمولة التلوث لكل من الـ TP&TNضمن الحوض الساكب للبحيرة TP=11543kg/yr 61367 kg/yr, = TN كما تبين أن نسبة مساهمة المصادر غير النقطية في حمولة التلوث 80% و20% للمصادر النقطية بالنسبة للفوسفور أما بالنسبة للنتروجين فإن نسبة مساهمة المصادر غير النقطية في حمولة التلو ث 75% و25% للمصادر النقطية. The water quality in Al Thawra Lake was getting worst recently because of the increscent of the concentration of nutrients, which reached the lake from point and nonpoint sources. The Geographic Information System GIS was widely used in the last decades in evaluating quality of water depending on models operates within GIS one of these models is The BASIN software (Best Assessment Science Integrating Point and Nonpoint sources)which used in this research .The Pload model(Pollution load) which is one of the BASIN models was used to estimate the pollution loads. The Pload was run by using satellite image, Digital Elevation Model (DEM30), land use map, and export coefficient values. The result showed that the total annual pollution loads of TP&TN are TP=11543 kg/yr, TN= 61367 kg/yr that came out of the watershed of the lake, Open maki and rock out crops are the dominate contributors to TP load in the watershed for about 30 %of total TP load, while Olives and citruses are the dominate contributor to TN load in the watershed for about 33 %of total TN load, the model results also indicated that the nonpoint sources are the main contributor to TP&TN loads in the watershed for about 80%of the total TP loads while only 20% from point sources, and for about 75%of the total TN loads from nonpoint sources while only 25% from point sources.